2020
DOI: 10.1042/bsr20194027
|View full text |Cite
|
Sign up to set email alerts
|

A biochemical comparison of the lung, colonic, brain, renal, and ovarian cancer cell lines using 1H-NMR spectroscopy

Abstract: Cancer cell lines are often used for cancer research. However, continuous genetic instability-induced heterogeneity of cell lines can hinder the reproducibility of cancer research. Molecular profiling approaches including transcriptomics, chromatin modification profiling, and proteomics are used to evaluate the phenotypic characteristics of cell lines. However, these do not reflect the metabolic function at the molecular level. Metabolic phenotyping is a powerful tool to profile the biochemical composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The alteration of tumor metabolism is closely related to the occurrence and progression of tumors (3). Tumor metabolism is generally characterized by increased lactic acid levels and decreased glutamine levels in blood circulation, and key enzymes in the metabolism of these substances have emerged as potential therapeutic targets (4). The advancement of metabolomics technology has led to the discovery of new and valuable differentially abundant metabolite (5)(6)(7)(8)(9), such as branched-chain amino acids (BCAAs).…”
Section: Introductionmentioning
confidence: 99%
“…The alteration of tumor metabolism is closely related to the occurrence and progression of tumors (3). Tumor metabolism is generally characterized by increased lactic acid levels and decreased glutamine levels in blood circulation, and key enzymes in the metabolism of these substances have emerged as potential therapeutic targets (4). The advancement of metabolomics technology has led to the discovery of new and valuable differentially abundant metabolite (5)(6)(7)(8)(9), such as branched-chain amino acids (BCAAs).…”
Section: Introductionmentioning
confidence: 99%
“…Research connecting metabolic findings to the cellular and molecular underpinnings of higher-grade glioma biology has previously been done with glioblastoma cells lines, which showed high variability in metabolites as measured by MRSI and cell culture metabolites. 38 A similar study has not been done for LrGGs. Several studies have shown considerable upregulation of genomic and transcriptomic components of gliomas pertaining to metabolic pathway enzymes such as lactate dehydrogenase and creatine kinase with levels increasing with glioma grade.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, colon cancer cell lines showed increased levels of lactate, isovalerylcarnitine, and isobutiyrilcarnitine (degradation products of isoleucine and valine, respectively) [7] . Hu et al [51] compared the metabolic profiles of different tumor cell lines using MS. The distinct metabolic profile of each cell line was characterized by a unique phenotype.…”
Section: Metabolic Profile Of Cancer Cellsmentioning
confidence: 99%
“…However, intracellular analysis showed high glutamate concentrations in both RCC and SKOV3 cells, compared with those in other cells. Furthermore, lung cancer cells (A549) released higher concentrations of lactate but lower alanine levels, whereas brain tumor cells (H4) released high levels of serine, methionine, threonine, valine, glycine, and acetate [51] .…”
Section: Metabolic Profile Of Cancer Cellsmentioning
confidence: 99%